2006
DOI: 10.1016/j.cardiores.2006.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nox inhibitor VAS2870 attenuates PDGF-dependent smooth muscle cell chemotaxis, but not proliferation☆

Abstract: VAS2870 effectively suppresses growth factor-mediated ROS liberation in VSMC. Furthermore, it completely inhibits PDGF-dependent VSMC migration, whereas it does not affect DNA synthesis. These divergent effects reflect the critical role of Src activity, which-in contrast to Akt and Erk-appears to be redox-sensitive and is absolutely required for PDGF-induced chemotaxis, but not cell cycle progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
165
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(173 citation statements)
references
References 44 publications
7
165
0
1
Order By: Relevance
“…Multiple sources of ROS have been implicated in migration. The novel Nox inhibitor VAS2870 attenuates PDGF-induced migration (Ten Freyhaus et al 2006). Furthermore, in vivo studies have shown that remodeling is delayed in p47phox−/− mice and is completely abolished in mice lacking eNOS, suggesting that early remodeling requires NADPH oxidasederived ROS, while late remodeling is more dependent on ONOO • generated by eNOS (Castier et al 2005).…”
Section: Vascular Smooth Muscle Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sources of ROS have been implicated in migration. The novel Nox inhibitor VAS2870 attenuates PDGF-induced migration (Ten Freyhaus et al 2006). Furthermore, in vivo studies have shown that remodeling is delayed in p47phox−/− mice and is completely abolished in mice lacking eNOS, suggesting that early remodeling requires NADPH oxidasederived ROS, while late remodeling is more dependent on ONOO • generated by eNOS (Castier et al 2005).…”
Section: Vascular Smooth Muscle Cell Migrationmentioning
confidence: 99%
“…Rapamycin, a relatively new immunosuppressant that acts on the protein synthesis mediator mTOR, inhibits PDGF-induced proliferation without affecting ROS production (Park et al 2005). Furthermore, although PDGF-induced migration is inhibited by the novel Nox inhibitor VAS2870, this inhibitor has no effect on DNA synthesis (Ten Freyhaus et al 2006). Whereas these latter observations could be used to support the concept that both ROS-sensitive and ROS-insensitive signaling pathways mediate PDGF-induced proliferation, we have not been able to demonstrate a requirement for ROS in PDGF-induced growth in these cells (unpublished observations).…”
Section: Vascular Smooth Muscle Proliferationmentioning
confidence: 99%
“…VAS2870 (3-bezyl-7-(2-benzoxazolyl)thio-1,2,3-triazolo(4,5-d)pyrimidine] was discovered via a high-throughput screening assay specific for NAD(P)H oxidase activity at Vasopharm Biotech. Its unique property is that it can inhibit agonist-induced NAD(P)H activity but not the basal activity of this enzyme complex, suggesting specificity within the NAD(P)H oxidase family [e.g., Nox1 activation by PDGF is inhibited, but Nox4 activity at basal level in VSMCs is unaffected (322)]. However, a screening for Nox specificity has not been conducted.…”
Section: Phycobilinsmentioning
confidence: 99%
“…10 Pharmacological inhibitors of Nox4 (VAS2870 and GKT136901) also prevented agonist-induced oxidative stress and inflammatory responses in cultured cells. 11,12 However, these observations are merely suggestive of Nox4 in vascular pathology and by no means establish cause and effect.…”
Section: Article See P 1217mentioning
confidence: 92%
“…First, in the study of Schroder et al, 14 vascular functional studies were performed in large conduit vessels (aorta) and in lung endothelial cells from Nox4-deficient mice, whereas many previous studies explored small arteries and cultured vascular smooth muscle cells. 3,5,9,10,11,17,18 Second, in Nox4 knockout mice, the gene deletion is global, and, accordingly, it is not entirely correct to implicate a vascular-specific pathology in a model in which there is a ubiquitous knockout. Third, the fact that it is only in challenged conditions that Nox4 knockout mice exhibit a vascular phenotype indicates a nonessential role of Nox4 in physiological conditions.…”
Section: Article See P 1217mentioning
confidence: 99%